Why are there virtually no mandatory open access policies at American universities?. Issue 3 (20th June 2016) - Anderson, Rick
Abstract : Key points U.S. university OA policies are far less mandatory than those in the U.K. The waiver clauses in U.S. university policies make it easy for authors to decline making their articles OA. The relative autonomy – and competitiveness – of U.S. universities may be the reason for weaker OA policies. OA in the U.S. is likely to be driven by government funding agency policies rather than by academia.